A comparative study on the validity and reliability of anterior, medial, and posterior approaches for internal fixation in the repair of fractures of the coronoid process of the ulna - Hong-Wei Chen; Xiao-Feng Teng (European Journal of Medical Research, 2018)
Abstract Background The coracoid process plays an important role in maintaining the stability of the elbow joint. A fracture of the coronoid process is often treated via surgical approaches, including open reduction and internal fixation, which aim to regain a stable, flexible, and loadable joint. In this study, we compared the anterior, medial, and posterior approaches of internal fixation in the repair of fractures of the coronoid process of the ulna. Methods In this retrospective study, 147 patients with fractures in the coronoid process of the ulna were recruited and classified into the anterior group (n = 73), the medial group (n = 32), and the posterior group (n = 42) according to the surgical approach used for internal fixation. These patients were assessed with respect to incision, operative time, estimated blood loss, fracture healing, and postoperative complications. The Mayo Elbow Performance Score was used to evaluate any form of disability associated with elbow injuries. Multivariate logistic regression analysis was performed to investigate the factors influencing the efficacy of fractures of the coronoid process of the ulna. Results In the medial approach group, the operative time was longer, and perioperative blood loss and postoperative drainage volume were obviously increased compared with the anterior and posterior groups. The anterior group exhibited a better postoperative recovery compared with the medial, and posterior groups. Compared with the anterior group, fracture-healing time in the posterior group was further reduced, whereas elbow joint flexion extension and forearm rotation degree improved. Complications were significantly reduced in the posterior approach group compared with the anterior and medial groups. The factors influencing the efficacy of fractures of the coronoid process of the ulna included the Regan–Morrey classification, perioperative blood loss, and the internal fixation approach. Conclusion In summary, the approach used influences fracture healing or the outcome after osteosynthesis. The posterior internal fixation method produced satisfactory functional outcomes in patients with fractures of the coronoid process of the ulna.